Stereotactic body radiation therapy combined with cadonilimab and lenvatinib in the treatment of hepatocellular carcinoma with Vp3 or Vp4 portal vein tumor thrombus: a prospective, multicenter, single-arm, phase II clinical trial - Mo, Ning; Hu, Kai; Zeng, Zhiming; Yang, Lihua; Fang, Yeying; Zeng, Jie; Li, Ye; Yang, Zhendong; Tang, Jing; Zhang, Tingting; Ma, Fuchao; Liu, Cuizhen; et al. (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) exhibit a dismal prognosis, occurring in 44%–62.2% of cases at initial diagnosis. The optimal treatment for this population remains undefined.MethodsIn this prospective, multicenter, single-arm phase II trial across three Chinese centers, eligible HCC patients with Vp3/4 PVTT received combined stereotactic body radiotherapy (SBRT), cadonilimab, and lenvatinib. Primary endpoint was objective response rate (ORR) in primary liver lesions (RECIST v1.1/mRECIST); secondary endpoints included ORR in PVTT, progression-free survival (PFS), overall survival (OS), duration of response (DOR), and safety.ResultsOf 24 enrolled patients, 21 were evaluable for efficacy. ORR for primary lesions was 38.1% (RECIST v1.1) and 47.6% (mRECIST), with a disease control rate (DCR) of 100% by both criteria. For PVTT, ORR and DCR were 76.2% and 100%, respectively. At a median follow-up of 19.7 months, median PFS was 6.8 months (95% CI: 4.6–12.9), DOR was 10.4 months (95% CI: 2.9–NE), and OS was 13.4 months (95% CI: 6.8–NE). Early biomarker declines (≥75% AFP reduction or ≥50% PIVKA-II decline at 6 weeks) correlated with superior outcomes: AFP reduction predicted longer PFS (HR=0.22, p=0.006) and OS (HR=0.25, p=0.024); PIVKA-II reduction similarly predicted PFS (HR=0.28, p=0.007) and OS (HR=0.18, p=0.002). Common treatment-related adverse events (TRAEs) included hypertension (50%), thrombocytopenia (42%), and fatigue (38%).ConclusionsThe combination of SBRT, cadonilimab, and lenvatinib showed promising efficacy and manageable toxicity in HCC patients with Vp3/4 PVTT. Early AFP or PIVKA-II response at 6 weeks may serve as a prognostic biomarker.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT06040177.